Encouraging a continuing personal investment in learning : motivation as an instructional outcome - Maehr, Martin L. (Emerald Publishing Limited : Information Age Publishing Inc., 2012)
The writing of this book was in part supported by a grant from the National Science Foundation (NSFEHR 0335369). It represents a significant extension and enriched interpretation of earlier work on "motivation as an instructional outcome" (e.g., Maehr, 1976). Such enrichment and enhancement was prompted by the work on the project as it was conceptualized and envisioned by Paul Pintrich---and later, following his untimely death, carried out by a cadre of students and colleagues, including especially his Wife, Life Partner and also oft-time collaborator in multiple research and scholarly endeavors: Dr. Elizabeth DeGroot as well as several colleagues, including, the author of this volume and Dr. Stuart Karabenick.Of course, it is the primary author of this volume who must bear the responsibility for omissions, errors and interpretations that may have slipped into the text. But whatever portions of this volume may be deemed worthy of consideration and possibly of some value for fellow scholars presently or in the future --- and also contribute in at least some small way not only to continuing scholarly study of "The Most important attitude that can be formed: "That of Desire to go on Learning." But therewith here and there also prove useful not only for scholars and the development of an increased understanding of the nature and nurture of motivation and its impact on the pursuit of knowledge but also prove useful to students in preparing to become educators --- and perhaps also of value to experienced educational practitioners ---- and here there maybe also to parents and others with a concern for the nature and nurture of excellence in teaching and learning.